2013
DOI: 10.1530/jme-13-0090
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia upregulates the gene expression of mitochondrial aconitase in prostate carcinoma cells

Abstract: Hypoxia induces metabolic alteration in cancer cells by stabilizing hypoxia-inducible factor 1a (HIF-1a (HIF1A)), which regulates the bioenergetic genes of glycolysis and lipid metabolic pathways. However, the target genes of hypoxia-induced metabolic alterations in the prostate remain uncertain. Mitochondrial aconitase (mACON) (ACONM) is an enzyme that is central to carbohydrate and energy metabolism and is responsible for the interconversion of citrate to isocitrate as part of the citric acid cycle in the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…Those enzymes include phosphofructokinase, phosphoglycerate mutase, pyruvate kinase, 6-phosphogluconate dehydrogenase, pyruvate dehydrogenase and aconitase39404142434445. Previously unknown regulation events include a retention of glucose-6-phosphate, an increased production rate of PRPP (5-Phospho-alpha-D-ribose 1-diphosphate) and a strongly accelerated production of glyceraldehyde 3-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Those enzymes include phosphofructokinase, phosphoglycerate mutase, pyruvate kinase, 6-phosphogluconate dehydrogenase, pyruvate dehydrogenase and aconitase39404142434445. Previously unknown regulation events include a retention of glucose-6-phosphate, an increased production rate of PRPP (5-Phospho-alpha-D-ribose 1-diphosphate) and a strongly accelerated production of glyceraldehyde 3-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, activation of SREBP-2 mainly activates transcription of cholesterol biosynthesis genes (Pai et al 1998, Horton et al 2003). Importantly, FAS expression is increased under hypoxia (Tsui et al 2013, Furuta et al 2008), and hypoxia up-regulates the synthesis of SREBP-1, but not SREBP-2 (Li et al 2007, Furuta et al 2008). Putative involvement of SREBP-1 in this regulation is consistent with our finding that synthesis of all acyl-containing lipid classes, but not Ch was increased in neurons under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that HIF1α generally upregulates lactate dehydrogenase A, mitochondrial aconitase, and more specifically fatty acid synthase in high grade tumors [192]. Corroborating this result -arrestin 1 is up-regulated in high grade prostate cancer and stabilizes HIF1α, which is connected to a reduction of succinate dehydrogenase A, fumarate hydratase, dihydrolipoamide dehydrogenase, dihydrolipoyl transacetylase and pyruvate dehydrogenase [193].…”
Section: Genetic Drivers Signaling and Microenvironment In Prostate mentioning
confidence: 94%